Pedagogical dimension of swim training as perceived by swimmers and their coach - Bartłomiej Lassek (Kazimierz Wielki University, 2022)
This article presents the educational benefits and drawbacks of competitive swimming training as assessed by the surveyed swimmers and their coach. The paper addresses issues concerning the formation of moral, aesthetic, intellectual and health attitudes in competitive swimmers through sports training. The purpose of this study is to identify their opinions regarding the impact of competitive swimming on the development of selected character traits. The study included 33 competitive swimmers (14 - women, 19 - men) and the coach of the competitive swimming section of the AZS Politechnika Lodzka sports club. The training seniority of the subjects is: 16 athletes - 6 - 10 years and 17 athletes 11 -17 years. The competitive section of the surveyed swimmers carried out training at the swimming pool of the ACSD sports complex "Zatoka Sportu" in Lodz. The study was conducted using a quantitative diagnostic survey method and qualitative focus interview technique. . The tools that were used in the study for the survey questionnaire and interview questionnaire. The article presents the results of our own research along with the results of other authors' research for discussion. The results of the study indicate that the practice of swimming by competitive athletes affects their educational process, where one of the important factors is the specificity of the sport. The article presents only a part of the pilot study, the results of which form the basis for the study proper.